Editorial [Hot Topic: Essential Fatty Acids (Guest Editor: Undurti N. Das)] - Das, Undurti N. (Current Pharmaceutical Biotechnology, 2006)
This special issue of Current Pharmaceutical Biotechnology deals with an exciting topic: &ldquoEssential Fatty Acids” and their implications for human health. Essential fatty acids (EFAs) are the main constituent of the phospholipid component of all cell membranes in the human body. EFAs, as it name implies, are essential for human survival but cannot be synthesized by the human body and hence, have to be obtained in our diet. The two EFAs are linoleic acid (LA) and -linolenic acid (ALA). Both LA and ALA form precursors to several of their long chain metabolites. Some of the important molecules that are formed from EFAs and their long-chain metabolites include: various eicosanoids, lipoxins, resolvins, and protectins. These molecules have several important actions on vascular tissue, platelets, leukocytes, macrophages, bronchial smooth muscle, myocardium, kidney, brain, and other cells and tissues in the body. Depending on the local tissue concentration and the type of metabolite formed from EFAs, they can have useful and harmful actions. For instance, excess formation of leukotrienes may produce inflammation, bronchospasm and thus may cause bronchial asthma. On the other hand, formation of appropriate amounts of lipoxins and resolvins may help in the resolution of inflammation and healing of wounds. In addition, EFAs may interact with nitric oxide and form nitrolipids that have potent biological actions. EFAs and their metabolites seem to have an important role in brain growth and development and memory formation and consolidation, participate in a variety of physiological and pathological processes. In this issue, the metabolism, actions and uses of EFAs and their metabolites has been outlined by various authors. I hope that the topics discussed will be useful to many of the readers.